Academic trajectories and labour market transitions of mature graduates: a case study from the University of Algarve - Gonçalves, Teresa (2014)
The Bologna Process, recently implemented in Portugal, has brought many changes to higher education institutions (HEI). One of these changes refers to a law that enables mature students (23 years and older) to gain special access to higher education, taking into account their professional experience. The numbers of mature students are therefore increasing in our country, making our academic population more diverse. Our team has in the past investigated these students’ situation in higher education (HE), in order to provide university management our recommendations to improve students’ success. To continue our research we (two HEI in Portugal) designed a new research project , which partially aims to understand mature students’ trajectories through HE and their transitions to the labour market. Again we hope to provide recommendations for that university management to do more for our students’ employability. In this paper we identify and characterise various dimensions of individual and collective profile of mature students in the University of Algarve (Portugal) and their paths towards labour market integration. Our results show that positive experiences within university context, regarding their learning and competences acquisition. Also it becomes clear that while studying in university mature students developed personal qualities that proved to be determinant to their professions or to the ability of creating their own businesses.